Kajian Awal Penentuan Daerah Prospek Panas Bumi di Gunung Bur Ni Telong berdasarkan Analisis Data DEM SRTM dan Citra Landsat 8 - Lukmanul Hakim; Nazli Ismail; Faisal Faisal (Jurnal Rekayasa Elektrika, 2017)
Research for a preliminary study of Bur Ni Telong, geothermal area, Bener Meriah district using remote sensing techniques has been done. The aims of the research were to determine the morphological condition based on the fault and fracture (FFD) map from the interpreted digital elevation model (DEM) shuttle radar topography mission (SRTM) and to know the vegetation density and surface temperature distribution using Landsat 8 image. The DEM SRTM data were analyzed using the lineament pattern which related to faults and fractures. The vegetation density was calculated using normalized difference vegetation index (NDVI) transformation. The estimated surface temperature was used to locate temperature anomaly. Referring to the geographical map, the dense class area include Silih Nara-Ketol-Peulimbang to Peudada, Juli to Sawang, and Bandar area. The fault and fracture dominantly have directions in East-West and Northwest-Southeast. While based on NDVI map we conclude that the area is covered by dense vegetation, dominated by intermediate to dense of vegetation. The LST map shows the location of maximum surface temperature values are in agreement with residential areas and uncovered areas, as in the areas of Simpang Tiga Redelong and Takengon. Some geothermal manifestations are located in sparse to intermediate vegetation areas with high temperature.